Principles of Sustainable Energy Systems, Second Edition. - Kreith, Frank (Mechanical and Aerospace Engineering Series., 2013)
... ""This is an ideal book for seniors and graduate students interested in learning about the sustainable energy field and its penetration. The authors provide very strong discussion on cost-benefit analysis and ROI calculations for various alternate energy systems in current use. This is a descriptive book with detailed case-based analyses of various systems and engineering applications. The text book provides real-world case studies and related problems pertaining to sustainable energy systems.""--Dr. Kuruvilla John, University of North Texas""The new edition of ""Principles of Sustainable En.